Characteristics and Outcomes of Pars Plana Vitrectomy for Proliferative Diabetic Retinopathy Patients in a Limited Resource Tertiary Center over an Eight-Year Period. (17th March 2019) - Choovuthayakorn, Janejit; Khunsongkiet, Preeyanuch; Patikulsila, Direk; Watanachai, Nawat; Kunavisarut, Paradee; Chaikitmongkol, Voraporn; Ittipunkul, Nimitr
Abstract : Purpose . To report characteristics and visual results in patients with PDR-associated complications following pars plana vitrectomy (PPV) in a tertiary center over an eight-year period. Methods . Medical records of diabetic retinopathy patients receiving PPV between January 2007 and December 2014 for PDR-related complications were reviewed. Results . A total of 890 consecutive PDR patients were included in the study. PPVs were performed for tractional retinal detachment (36.6%), persistent vitreous hemorrhage (VH) (35.4%), combined tractional and rhegmatogenous retinal detachment (14.5%), and vitreoretinal abnormalities (13.5%), respectively. Preoperative intravitreal bevacizumab injection (IVB) within two weeks prior to PPV and 23G vitrectomy systems was found to decrease the risk for intraoperative retinal break development (P = 0.045 andP = 0.015, respectively). The incidence of early dense postoperative VH decreased significantly with the administration of preoperative or intraoperative IVB at the end of PPV. Postoperative visual results significantly correlated with the initial visual acuity level, intraoperative retinal break development, and retained silicone oil tamponade at the final visit (P < 0.001, P = 0.040, andP = 0.044, respectively). Administration of adjuvant IVB either before or at the end of PPV had no significant association with the final visual outcomes. Conclusions . This study reported an improvement in visual acuity in nearly half of patients receiving PPV for PDR-associated complications in a limited resource center. The incidence of intraoperative retinal break and early postoperative VH decreased significantly with the application of IVB injections. Poor final visual outcomes were related to the lower initial visual acuity levels, intraoperative retinal breaks, and postoperative retained silicone oil.